Electrochemical rate constants in room temperature ionic liquids: the oxidation of a series of ferrocene derivatives. - Fietkau, N; Clegg, A; Evans, R; Villagrán, C; Hardacre, C; Compton, R (2006)
The high-speed channel electrode has been used to measure heterogeneous electron-transfer rates, k0, for a series of ferrocene derivatives in room temperaure ionic liquids (RTILs) under steady-state conditions thus avoiding the problems of ohmic drop and capacitative currents associated with transient methods. The figure shows the three-dimensional surface plot for k0 versus the transfer coefficient, α. © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.